(C)CAPM vs CAPM: Which model better reflects the performance of stocks in emerging markets? - Chang Medina, Alfonso (2018)
The CAPM is one of the main models in asset pricing due to its simplicity of calculation and popularity into academics and practitioners. However, the empirical evidence has shown its weakness in explaining the stylized facts -behaviors observed in the data- of cross section of the performance of stocks. One of the current theoretical proposals that overcomes the weaknesses of the CAPM is the (C) CAPM, which is a merger of the CAPM and the approach Consumption-based Asset Pricing Model. Since it takes the best of both models, the (C) CAPM has shown better performance for the US data. However, the question remains whether this performance is just as good or better in emerging markets. In this research we answer this question using data for the MILA (Integrated Latin American Market). Likewise, we evaluated the model at an aggregate level (Peru, Mexico, Colombia, and Chile) and sectorial level. The results of this research are complementary to what exists in the literature and would provide a better understanding of the behavior of the performance of the stocks to the academic environment and to the regulatory authorities.